The Political Economy of a Collusive Urban Regime: Making Sense of Urban Development Projects in Rome - Edoardo Esposito; Giulio Moini; Barbara Pizzo (Partecipazione e Conflitto, 2021)
The relative hegemony of land rentiers and real estate developers over the process of urban socio-economic reproduction is a defining characteristic of the "collusive regime" of Rome. Through the analysis of a case study, we tried to establish if the realisation of Urban Development Projects in this regime favours the unequal distribution of the benefits deriving from urban development. Applying a neo-Gramscian lens to urban political economy, we identified an interpretative model for explaining the role of UDPs in the urban regime of Rome. First, UDPs are suitable occasions for realising accumulation strategies based on the capture of rent gaps and the valorisation of urban assets. Second, the actors involved in UDPs mobilise ideational and material resources for gathering consensus for a project, that rewards their specific interests, by framing their investment as the best solution for localised collective needs. UDPs in Rome, therefore, facilitate the concentration of benefits and the generalisation of costs of urban development. Our research contributes to the understanding of Rome's fragile trajectory of growth and offers insights on the mechanisms reinforcing unequal urban development.